Traditional Herbal Medications Utilized in the Indian Medical System for the Management of Diabetes: An Updated Review and Clinical Implications - Sachan, Kapil; Verma, Suryakant; Arora, Kunal; Bharti, Ujjwal; Singh, Pranjal K.; Singh, Smita (Current Diabetes Reviews, 2024)
Phytomedicine, also called botanical medicine, is the practice of using plants to treat disease. Diabetes, for example, has been treated and prevented with herbal medication for a lot longer than Western medicine. Worldwide, diabetes has become a major health concern. The management of diabetes and hyperglycemia, two of the most common public health threats, is far from ideal. When hyperglycemia persists or is not under control, diabetes-related complications, like blindness, lower limb amputations, renal disease, and cardiovascular disease, play a significant role in the morbidity and mortality of the disease. Although chemicals and biochemical agents can assist in managing diabetes, there is currently no complete cure for the disease. Herbal remedies are one of many methods that can be used to treat and prevent diabetes and its subsequent problems. Numerous traditional treatments have been discovered for diabetes as a result of extensive research efforts. However, there are many factors to consider when deciding which herbs to use, such as the patient's financial status, the presence or absence of co-morbidities, and the accessibility, cost-effectiveness, and safety profile of the herbs. This article focuses on the use of herbal and natural remedies in the treatment and prevention of diabetes, the mechanisms by which these remedies lower blood glucose levels, and the specific herbal items now utilized in the management of diabetes.
Keywords: insulin